1992
DOI: 10.1002/ijc.2910500608
|View full text |Cite
|
Sign up to set email alerts
|

Basal‐cell carcinoma in temperate and tropical Australia

Abstract: The clinical features of patients with basal-cell carcinoma (BCC) living in temperate and tropical Australia were studied. In the temperate zone the patients were considerably older on average, men outnumbered women and there were differences between the sexes in the site of the prevalent BCC. In the tropics the patients were significantly younger on average, the male-to-female ratio approached unity and there were no differences between the sexes with regard to the site of the BCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…However, it should be noted that family physicians traditionally refer patients with skin cancer to dermatologists, and as there is a universal health insurance scheme in Australia, there is no disincentive for patients to seek treatment. In addition, a large survey of patients with skin cancer, carried out by the authors over the same time, found that the average age of patients with skin cancer, the ratio of basal to squamous cell carcinomas, the ratio of male to female patients and the sites of the prev alent skin cancers were similar to those found in other Aus tralian and overseas surveys of skin cancer [12,14,15]. The survey also detected that more skin cancers are devel oping on the trunk and that there has been a reversal of the sex ratio of patients with skin cancer in people born since the Second World War [16).…”
Section: Discussionmentioning
confidence: 58%
“…However, it should be noted that family physicians traditionally refer patients with skin cancer to dermatologists, and as there is a universal health insurance scheme in Australia, there is no disincentive for patients to seek treatment. In addition, a large survey of patients with skin cancer, carried out by the authors over the same time, found that the average age of patients with skin cancer, the ratio of basal to squamous cell carcinomas, the ratio of male to female patients and the sites of the prev alent skin cancers were similar to those found in other Aus tralian and overseas surveys of skin cancer [12,14,15]. The survey also detected that more skin cancers are devel oping on the trunk and that there has been a reversal of the sex ratio of patients with skin cancer in people born since the Second World War [16).…”
Section: Discussionmentioning
confidence: 58%
“…However, it should be noted that family physicians traditionally refer patients with skin cancer to dermatologists and, as there is a universal health insurance scheme in Australia, there is no disincentive for people to seek treatment. In addition, a large survey of skin cancer carried out by the authors over the same period found that the average age, ratio of men to women, ratio of basal to squamous cell carcinoma, and sites where the skin cancers were found were similar to surveys from Australia, New Zealand, North America and Europe [13,19]. The pa tients with skin cancer seen by Australian dermatologists are representative of people with skin cancer.…”
Section: Discussionmentioning
confidence: 96%
“…They were out-patients seen in private practice and at the Repatriation General Hospital. Heidelberg, and could be considered to be typical of an Australian dermatologist's practice [13]. The information recorded included age, sex, site of the cancer and histological diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…Although male dominance in NMSC is reported more often in the literature, there is no any difference in gender in Italian and Australian patients (14,15). Male/female Ağırgöl and Bozkurt.…”
Section: Discussionmentioning
confidence: 92%